2019
DOI: 10.29312/remexca.v10i7.1627
|View full text |Cite
|
Sign up to set email alerts
|

Ácido salicílico induce tolerancia al estrés por criogenia en Solanum tuberosum

Abstract: Un problema común en los procesos criogénicos es la supervivencia a temperatura ultra baja (-196 °C). Con base a los efectos fisiológicos del ácido salicílico (AS) en la señalización de respuestas de tolerancia a estrés, el objetivo fue evaluar el efecto de AS en el incremento de la supervivencia y en el crecimiento de yemas de papa sometidas a criogenia. Microplantas del clon avanzado 06-27 del Banco de Germoplasma in vitro del Programa de Papa en Metepec Estado de México, México, fueron incubadas por 28 días… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In parallel, Solanum tuberosum , and the method will be adapted to other potato cultivars prone to contagion. Moreover, Ayala-Hernandez et al [ 150 ] demonstrated that SA induces stress tolerance to which explants are subjected during cryopreservation. Pretreatment with 10 −6 and 10 −5 M SA provided significantly greater survival of explants to cryogenics (2.17–3.21 times with respect to the control).…”
Section: Cryopreservation Applications Of Agronomic Interestmentioning
confidence: 99%
“…In parallel, Solanum tuberosum , and the method will be adapted to other potato cultivars prone to contagion. Moreover, Ayala-Hernandez et al [ 150 ] demonstrated that SA induces stress tolerance to which explants are subjected during cryopreservation. Pretreatment with 10 −6 and 10 −5 M SA provided significantly greater survival of explants to cryogenics (2.17–3.21 times with respect to the control).…”
Section: Cryopreservation Applications Of Agronomic Interestmentioning
confidence: 99%
“…A recent investigation demonstrated a positive effect of 40 µM SA on olive somatic embryogenesis if applied with a cytokinin-like compound (TDZ + BAP) [ 140 ]. SA’s effect on inhibiting cell-to-cell communication and reducing water content in plant cells is an effective way to increase cell viability and dehydration tolerance required for successful cryopreservation [ 141 , 142 ].…”
Section: Major Aspects Of Plant Regenerationmentioning
confidence: 99%